Comparative Study of Chat GPT and traditional algorithms for Supporting Investment Decision Making - Petráň, Adam (2025)
The thesis explores ChatGPT-4o capabilities in financial portfolio management, using the FTSE 100 Index as a benchmark, and com-pares its performance to traditional methods like Mean-Variance Op-timization and Hierarchical Risk Parity. ChatGPT demonstrated strong stock selection skills, often outperforming the FTSE 100 In-dex, but faced challenges in precise weight allocation and data transparency. The findings underscore AI's potential as a comple-mentary tool in finance while highlighting the need for human oversight, with future research focusing on improving these limita-tions and assessing long-term applications.